Where Do Cancer Patients in Receipt of Home-Based Palliative Care Prefer to Die and What Are the Determinants of a Preference for a Home Death? - Cai, Jiaoli (Int J Environ Res Public Health, 2020)
Understanding the preferred place of death may assist to organize and deliver palliative health care services. The study aims to assess preference for place of death among cancer patients in receipt of home-based palliative care, and to determine the variables that affect their preference for a home death. A prospective cohort design was carried out from July 2010 to August 2012. Over the course of their palliative care trajectory, a total of 303 family caregivers of cancer patients were interviewed. Multivariate regression analysis was employed to assess the determinants of a preferred home death. The majority (65%) of patients had a preference of home death. The intensity of home-based physician visits and home-based personal support worker (PSW) care promotes a preference for a home death. Married patients, patients receiving post-graduate education and patients with higher Palliative Performance Scale (PPS) scores were more likely to have a preference of home death. Patients reduced the likelihood of preferring a home death when their family caregiver had high burden. This study suggests that the majority of cancer patients have a preference of home death. Health mangers and policy makers have the potential to develop policies that facilitate those preferences.